Analysis of Digital Marketing Implementation in Home Industry Gurilem Crackers in BatuJajar, West Bandung Regency - Khadijah Athahirah; Sri Damayanti; Keysha Audina; Miptahudin Kurniawan (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Abstract This study aims to analyze the implementation of digital marketing strategies in the home industry of Gurilem Crackers Batujajar, West Bandung Regency owned by Mrs. Komariyah in an effort to increase competitiveness and sales in the digital era. The main focus of this study is to identify sales of Gurilem Crackers with social media, namely Facebook, with the implementation of the COD (cash and delivery) system between buyers and sellers meeting each other in a place for transactions. This study uses a qualitative descriptive method with a case study approach on home-scale cracker industry players. The results of the analysis show that the use of digital platforms such as social media, namely Facebook, has a significant impact on product purchases, expanding market reach, and customer loyalty. The results of the study show that the main strength of the Gurilem cracker business lies in its distinctive taste that consumers like and its affordable price. In addition, direct interaction with consumers, as well as the use of digital promotion features, also strengthen the product's position in the market. However, challenges such as limited digital literacy, technical skills and unattractive packaging are still obstacles that need to be overcome through training and mentoring. Opportunities that can be utilized include increasing demand for traditional snacks and broad market potential through digital platforms. Threats faced include tight competition with similar products and fluctuations in raw material prices. Thus, digital marketing can be a strategic solution for the sustainable development of this Gurilem Cracker home industry amidst increasingly competitive market competition. Keywords: Digital marketing, Home industry, Social media